PENGARUH METODE MASERASI DAN SOKHLASI TERHADAP KANDUNGAN SENYAWA ANTIOKSIDAN DAUN Pluchea indica L. DENGAN METODE LC-MS - Afidatul Muadifah; Tilarso, Dara Pranidya; Sowe, Momodou Salieu; Tarigan, Indra Lasmana; Ngibad, Khoirul; Yuliantari, Sonia Devi (Chempublish Journal, 2024)
Pluchea indica L. is a plant have some secondary metabolite compounds namely flavonoids, alkaloids, tannins, saponins, terpenoids, and phenols that have antioxidants activity. The purpose of this study was to compare the content of antioxidant compounds analyzed using LC-MS and determine the relationship of antioxidant activity through the DPPH test on P. indica leaves extracted by maceration and soxhlation. The extracts from maceration and soxhlation of P. indica leaves were analyzed using LC-MS to determine the composition of the compounds contained therein then continued with the antioxidant activity test using the DPPH method. In the antioxidant activity test using DPPH, each extract was made 3 variations of concentration, namely 10 ppm, 50 ppm, and 100 ppm, and measured based on the absorbance of DPPH at a wavelength of 515 nm using a UV-vis spectrometer. The results of analysis using LC-MS on macerated extracts of P. indica leaves are 112 compounds consisting of flavonoids 72.4841%, phenols 9.00625%, terpenoids 6.11827%, alkaloids 6.99075%, tannins 2.2256%, and saponins 2.04458%. The Soxhlet extraction contained 116 compounds consisting of flavonoids 67.14345%, phenols 8.95854%, terpenoids 13.82165%, alkaloids 5.35637%, tannins 2.53305%, and saponins 0.2969%. The results of the antioxidant activity test using DPPH on maceration extracts have an IC50 value of 76.7576 and soxhlation 62.580 ppm. Both maceration and soxhlation extracts of P. indica leaves contain compounds that have high antioxidant potential and have good antioxidant activity, namely in the strong antioxidant category. However, the soxhlation extract has more compounds and a lower IC50 value. Thus, the more antioxidant compounds contained in an extract, the lower the IC50 value so that the better the antioxidant activity.